A Review of the National Gifted Standards Implementation in Eight Districts: An Uneven Picture of Practice. Issue 4 (October 2019) - VanTassel-Baska, Joyce; Hubbard, Gail Fischer
This article presents the results of a review of eight gifted programs, using the 2010 National Association for Gifted Children (NAGC) program standards as one basis for assessing the programs. Each of the six standards is reviewed in respect to the extent that programs addressed underlying indicators. Findings showed that districts met slightly over 50% of indicators for three standards. For the other three standards, only 31% to 37% of the indicators were met through district gifted programs. Areas of greatest need for further program development include developing planning tools for curriculum implementation, monitoring of program implementation efficacy, establishing the routine use of content acceleration in all subjects, and developing counseling support for gifted learners.